Shedding of porcine circovirus type 1 DNA and rotavirus RNA by infants vaccinated with Rotarix®. Issue 4 (3rd April 2017) - Mijatovic-Rustempasic, Slavica; Immergluck, Lilly Cheng; Parker, Trisha Chan; Laghaie, Elham; Mohammed, Anaam; McFadden, Terri; Parashar, Umesh D.; Bowen, Michael D.; Cortese, Margaret M.
ABSTRACT: Thirty-three infants aged ∼2 months had serial stool samples collected after receipt of Rotarix® vaccine dose 1, and were assessed for shedding of porcine circovirus type 1 DNA and Rotavirus group A RNA by molecular methods. We did not find strong evidence that porcine circovirus type 1 replication occurred. Porcine circovirus type 1 genome with the same sequence as that in Rotarix® was detected in a few infants as late as day ≥ 13; while this timing could suggest there may have been replication and not just transient passage through the gastrointestinal tract, the lack of increase in copy number in any infant supports transient passage and there are inherent limitations to the results. We found that 21% of infants did not shed Rotarix® RVA RNA beyond the day 3 sample, which may suggest lack of vaccine virus replication. Of the infants in whom Rotarix RVA RNA shedding continued, peak copy numbers were reached on days 3–5 for ∼40%, and after day 5 in ∼60%, and shedding can be prolonged (≥ 45 days).